Peen-forming : the possibility of technology transfer from aircraft industry to the production of high-speed ships - Markovina, Roko (Array, 2008)
Summary: Shot-peening is a widespread surface treatment method used to improve fatigue and stress corrosion resistance of many metals. From that technology the peen-forming method has emerged and has replaced traditional forming methods on many aircraft types, allowing wing designs to maximise strength to weight ratios. The new generation of high-speed ships and boats use similar lightweight building materials as aircraft industry, such as different aluminium alloys, which indicates that shot-peening and peen-forming methods could be introduced in shipbuilding industry. This paper describes peen-forming technology which is rarely present in shipbuilding, and shows why the peen-forming should be considered as an important ship production method that may replace more costly and complex forming technologies. The paper presents application techniques, process variables, limitations and applicable designs regarding peen-forming and concludes that peen forming will have a signifi cant role in the future of shipbuilding of fast and high-speed vessels